AN ANALYSIS OF ENGLISH LEARNING STRATEGIES TO THE EIGHTH GRADE STUDENTS OF JUNIOR HIGH SCHOOL 4 LUBUKLINGGAU - Sertika, Suci; Syaprizal, Syaprizal; Hamdan, Hamdan (ELite Journal : International Journal of Education, Language and Literature, 2024)
The objectives of this article was to describe what were English learning strategies applied by the eighth grade students of Junior High School  4 Lubuklinggau The method applied in this research was descriptive quantitative method. The subject of the research was all the eighth grade students of Junior High School 4 Lubuklinggau in academic year of 2022/2023. The number of the population was 244 students. The sample of this research was taken by using simple random sampling. The number of the sample was 30 students of class VIII.E. To get the data, the researcher used Oxford SILL questionnaires. The data were analyzed by describing students’ answer and dividing students’ English learning strategies into some categories: 1) Memory Strategies, 2) Cognitive Strategies, 3) Compensation Strategies, 4) Metacognitive Strategies, 5) Affective Strategies and 6) Social Strategies.  Based on the result of data analysis, the researcher found out data that: 1) 9 (30%) students as social strategies, 2) 8 (26.67%) students as memory strategy and 3) 7 (23.33%) students as affective strategy, 4) 3 (10%) students as metacognitive strategy, 5) 2 (6,67%) students as cognitive strategy and 6) 1 (3,33%) students as compensation strategy. In conclusion, social strategies was the most frequently strategies used by the students. Whereas, the least frequently learning strategies used by VIII.E class of Junior High School  4 Lubuklinggau was compensation strategy.